Multimarket Contact and Resource Dissimilarity: A Competitive Dynamics Perspective - Young, Greg; Smith, Ken G.; Grimm, Curtis M.; Simon, Daniel (Journal of Management, 2000)
Does the competitive dynamics perspective support the mutual forbearance (Edwards, 1955) and resource dissimilarity (Caves & Porter, 1977) theories of competitive behavior? This research examines competitive behavior in the U.S. software industry and finds: (1) as multimarket contact increases, a firm moves less frequently but more quickly following the moves of rivals; (2) as a firm’s resources are more dissimilar relative to rivals, it becomes more rivalrous along both action and timing dimensions of competitive behavior; and, (3) the influence of multimarket contact on firm-level action is most influential for firms whose resources are more dissimilar relative to rivals, but its influence on a firm’s time to move is most influential for firms whose resources are more similar relative to rivals. Thus, the dynamic perspective generally supports, but goes beyond, the insights of the established mutual forbearance and resource dissimilarity theories.